Research on Computer Interlocking System Simulation and Test Platform - Pei WANG (机车电传动)
Aiming at the problems of insufficient and inefficient testing of computer interlocking system by manual testing method, a design scheme of simulation test platform for automatic testing of interlocking system function was proposed. By analyzing the system structure and manual testing process of the interlocking system, the design idea and implementation mode of the simulation test platform were determined, and the automatic testing goal of interlocking function could be achieved finally.